2014
DOI: 10.4238/2014.october.20.22
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of DNA methylation patterns and levels in maize hybrids and their parents

Abstract: ABSTRACT. Heterosis is the superior performance of heterozygous individuals and has been widely exploited in plant breeding, although the underlying regulatory mechanisms still remain largely elusive. To understand the molecular basis of heterosis in maize, in this study, roots and leaves at the seedling stage and embryos and endosperm tissues 15 days after fertilization of 2 elite hybrids and their parental lines were used to estimate the levels and patterns of cytosine methylation by the methylation-sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
0
4
1
Order By: Relevance
“…In this paper, the MSAP technique was used in order to determine the level of DNA methylation in Z. mays under either water deficiency or Se treatment. The average of total relative cytosine methylation was 60.85% and was higher than that 26.15 and 32.15%, previously reported for maize leaves by Zhao et al (2007) and Yang et al (2011) , respectively, but it was lower than 68.55% reported in the same species by Sun et al (2015) .…”
Section: Discussioncontrasting
confidence: 64%
“…In this paper, the MSAP technique was used in order to determine the level of DNA methylation in Z. mays under either water deficiency or Se treatment. The average of total relative cytosine methylation was 60.85% and was higher than that 26.15 and 32.15%, previously reported for maize leaves by Zhao et al (2007) and Yang et al (2011) , respectively, but it was lower than 68.55% reported in the same species by Sun et al (2015) .…”
Section: Discussioncontrasting
confidence: 64%
“…On the other hand, if both parental alleles contribute equally to gene expression in a hybrid, they are said to exhibit additive behavior and the expression level of genes or proteins is equal to the average of both the parents referred to as the mid-parent value (MPV). High throughput methods have enabled the re-examination of the proportion of additive and non-additive expressions in heterosis, including analysis of quantitative trait loci (QTL; Li et al 2008;Meyer et al 2010;Shi et al 2011;Andorf et al 2012;Giraud et al 2014;Liu et al 2014a), gene expression (Song et al 2007;Stupar et al 2008;Ma et al 2011;Shen et al 2012;Qin et al 2013), genome-wide transcriptomics (Paschold et al 2012;Zhai et al 2013;Ding et al 2014;Paschold et al 2014;Zhiguo et al 2014;Groszmann et al 2015, Wang et al 2015, DNA methylation pattern analysis (Shen et al 2012;Liu et al 2014b), comparative proteomics (Dahal et al 2012;Wang et al 2014) and small and micro RNA transcriptomics (Ding et al 2012;Shen et al 2012;Li et al 2014;Zhang et al 2014;Xin et al 2015). However, none of the current genetic models sufficiently explain heterosis in polyploid plants, which is compounded by genomic dosage, complex allelic and genic interactions, and epigenetic regulation.…”
Section: Introductionmentioning
confidence: 99%
“…A reduction in methylation can also take place following a ‘genomic shock’, as seen in events like hybridization or allopolyploidization [ 28 ]. As an illustration, in maize, hybrids derived from two inbred lines exhibited decreased methylation levels in comparison to their corresponding inbred counterparts, with the highest degree of demethylation observed in the hybrids [ 29 ]. Similarly, in this study, the methylation levels in the F4 hybrids were found to be lower compared to the parental lines.…”
Section: Discussionmentioning
confidence: 99%